2007
DOI: 10.1038/sj.mp.4002100
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of 19 serotoninergic candidate genes in adults and children with attention-deficit/hyperactivity disorder identifies association for 5HT2A, DDC and MAOB

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common psychiatric disorder in which different genetic and environmental susceptibility factors are involved. Several lines of evidence support the view that at least 30% of ADHD patients diagnosed in childhood continue to suffer the disorder during adulthood and that genetic risk factors may play an essential role in the persistence of the disorder throughout lifespan. Genetic, biochemical and pharmacological studies support the idea that the serotonin syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
103
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 78 publications
6
103
1
1
Order By: Relevance
“…The association between ADHD and the DRD4 risk haplotype detected in the present study was observed in the combined but not in the inattentive clinical subtype. Our results are in agreement with previous studies supporting the validity of the different DSM-IV subtypes, mainly the combined subtype, and suggesting the participation of differential genetic factors in distinct ADHD clinical groups [Rasmussen et al, 2004;Larsson et al, 2006;Sobanski et al, 2008;Ribases et al, 2009]. Interestingly, Smith [2010] performed a meta-analysis of 28 association studies between ADHD and the 48bpVNTR in DRD4 and observed that increases in the proportion of combined ADHD patients within an ADHD sample were associated with an increase in the magnitude of the effect.…”
Section: Discussionsupporting
confidence: 92%
“…The association between ADHD and the DRD4 risk haplotype detected in the present study was observed in the combined but not in the inattentive clinical subtype. Our results are in agreement with previous studies supporting the validity of the different DSM-IV subtypes, mainly the combined subtype, and suggesting the participation of differential genetic factors in distinct ADHD clinical groups [Rasmussen et al, 2004;Larsson et al, 2006;Sobanski et al, 2008;Ribases et al, 2009]. Interestingly, Smith [2010] performed a meta-analysis of 28 association studies between ADHD and the 48bpVNTR in DRD4 and observed that increases in the proportion of combined ADHD patients within an ADHD sample were associated with an increase in the magnitude of the effect.…”
Section: Discussionsupporting
confidence: 92%
“…ADHD is a highly heritable and prevalent psychiatric disorder characterized by severe impairment in attention, hyperactivity and impulsivity (Banaschewski et al, 2010). Researchers reported that the DDC gene was strongly associated with ADHD in both childhood and adulthood (Ribases et al, 2009). A genome-wide association study also supported the association between the DDC gene and inattentive ADHD using over 900 ADHD Caucasian probandparent trios (i.e., International Multicenter ADHD Genetics [IMAGE] project dataset) (Lasky-Su et al, 2008).…”
mentioning
confidence: 79%
“…Moreover, the DDC gene was found to be related to ADHD inattention symptoms (Guan et al, 2009;Lasky-Su et al, 2008;Ribases et al, 2009). There was direct evidence of altered DOPA decarboxylase activity in children and adults with ADHD using the positron emission tomography (Ernst et al, 1998(Ernst et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of 5-HT 2A receptor signaling is implicated in several prevalent psychiatric disorders (6)(7)(8)(9)(10)(11), and the underlying effect of these alterations of serotonergic signaling may involve structural changes in synapses, which may alter neural circuits. Additionally, kalirin has reduced mRNA expression in the cortex of schizophrenia patients (42), and MUPP1 has been genetically associated with drug withdrawal seizures (43).…”
Section: Discussionmentioning
confidence: 99%